2012
DOI: 10.1002/sce.21010
|View full text |Cite
|
Sign up to set email alerts
|

Student learning through journal writing in a general education chemistry course for pre‐elementary education majors

Abstract: This paper describes research on the use of journals in a general education chemistry course for elementary education majors. In the journals, students describe their understanding of a topic, the development of that understanding, and how the topic connects to their lives. In the process, they are able to engage in reflection about several things. How the frequency and nature of those reflections relate to overall course outcomes, the content and quality of final exam essays on those topics, and student metac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Frequent and consistent reflective writing, in the form of journal entries or blogs, is a rich way by which students may contemplate and articulate their knowledge and skill development as they are learning a new subject (Stevens and Cooper, 2009; Bean, 2011; Dianovsky and Wink, 2012). These reflective writing assignments may help students articulate what they know, what they don't know, and what they need to learn.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Frequent and consistent reflective writing, in the form of journal entries or blogs, is a rich way by which students may contemplate and articulate their knowledge and skill development as they are learning a new subject (Stevens and Cooper, 2009; Bean, 2011; Dianovsky and Wink, 2012). These reflective writing assignments may help students articulate what they know, what they don't know, and what they need to learn.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that reflective writing improves students' metacognitive awareness and helps them become critical thinkers (Mezirow, 1990; Stevens and Cooper, 2009; Dyment and O’Connell, 2010; Bean, 2011; Dianovsky and Wink, 2012; Elbow and Sorincelli, 2014). Students regularly tasked with journaling have scored significantly higher on self‐regulated learning and reflective thinking scales, suggesting the process of journaling facilitates progression toward self‐regulated learning (Jado, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pedagogic research, journal writing has attracted attention for its potential to provide a non-threatening platform for personal contemplation on emerging understandings of a given topic (Casanave 2011). Our interest in journal writing pertains to its usefulness for encouraging participants to make connections between the academic content of a subject and personal experiences, observations, and other forms of prior knowledge that have often fallen beyond the purview of pedagogic research (Dianovsky and Wink, 2012;Pollock et al 2010). For this reason, students in our sample were encouraged to reflect both on their personal readings, as well as interaction with peers during class and tutorial discussions.…”
Section: Pedagogic Applications Of Journal Writingmentioning
confidence: 99%
“…Ed., 10(6), 625-634 response to, or analysis of an event, experience, or concept (Martin, 2000, cited in Chabon, 2012. According to many educators and previous studies, journal writing has many advantages and benefits, such as 1) Stimulating reflective thinking among students (Dianovsky & Wink, 2012;Dyment & O'Connell, 2011;Langer, 2002;Spalding & Wilson, 2002); 2) Being an effective teaching, learning and assessment tool (Chabon, 2012;Shin, 2006); 3) Improving students" learning and communication skills (Kostos & Shin, 2010;Talyor-Haslip, 2010;Harmelink, 1998); 4) providing a means for students to develop personally and professionally (Dyment & O'Connell, 2011;Rolfe, 2006); 5) Providing valuable feedback to students, showing growth and changes in their attitudes and knowledge over a term or a semester (Bolin, Khramtsova & Saarnio, 2005); 6) It can also be used to activate prior knowledge, engage the imagination, and practice writing skills (Fahsl & McAndrews, 2012), and 7) as a tool for self-awareness and empowerment (Blumenfeld, 2010).…”
mentioning
confidence: 99%